Umbilical Cord-Derived Mesenchymal Stromal Cells Contribute to Neuroprotection in Neonatal Cortical Neurons Damaged by Oxygen-Glucose Deprivation - Mukai, Takeo; Tojo, Arinobu; Nagamura-Inoue, Tokiko (Frontiers in Neurology, 2018)
Several studies have reported that human umbilical cord-derived mesenchymal stromal cells (UC-MSCs) restore neurological damage in vivo through their secretion of paracrine factors. We previously found that UC-MSCs attenuate brain injury by secreting neurotrophic factors, such as brain-derived neurotrophic factor (BDNF) and hepatocyte growth factor (HGF). However, how these factors contribute to neuroprotection remains unknown. In this study, we aimed to investigate to what extent UC-MSC-derived HGF and BDNF contribute to neuroprotection using a Transwell co-culture system of neonatal cortical neurons damaged by oxygen-glucose deprivation. The influence of HGF and BDNF were determined by investigating neurons in both the presence and absence of UC-MSCs as these cells consistently secrete both factors and can be blocked by neutralizing antibodies. In the co-culture, UC-MSCs significantly improved neuronal injury, as indicated by an increase in immature neuron number, neurite outgrowth, and cell proliferation. Co-culture of damaged neurons with UC-MSCs also exhibited a reduction in the number of neurons displaying signs of apoptosis/necrosis. The neuroprotective actions of UC-MSCs were partially reverted by neutralizing antibodies. Together, our findings reveal that UC-MSC-secreted HGF and BDNF have neuroprotective effects on damaged neurons. Further studies should address the existence of other potential neurotrophic paracrine factors.